Manajemen Pengendalian Risiko pada Proyek Pembangunan Gedung Perpustakaan Bandar Lampung dengan Metode IBPRP - Mauliana, Yunita; Kusuma, Adil Putra (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
Every construction project carries inherent risks that can lead to accidents, which may range from minor injuries to deadly incidents and even fatalities. To diminish the chances of work-related accidents at the project site, it is crucial to adhere to regulations pertaining to occupational health and safety (K3). This study seeks to identify potential hazards and evaluate risk factors associated with all activities in the Bandar Lampung Library Building Construction project, as well as to analyze risk control employing the HIRARC method (Hazard Identification, Risk Assessment and Risk Control). The findings from the risk matrix assessment prior to implementing risk control indicated 75 potential risk hazards, which included: 14 activities identified as extreme risk, 47 activities in the high risk category, 12 activities classified as moderate risk, and 2 activities deemed low risk. The activities with the most significant potential hazards include: roof installation and keet directors, casting work, iron installation work, and formwork work. Following the risk control process, modifications were made in the risk level for each type of work. There were 9 potential hazards classified as high risk, 11 potential hazards categorized as moderate risk, and 55 potential hazards grouped in the low risk category. This illustrates the significance of implementing risk control measures to ensure all potential hazards can be managed and reduced.